Transcatheter arterial chemoembolization combined with radiofrequency or microwave ablation for hepatocellular carcinoma: a review. (28th September 2018) - Galanakis, Nikolaos; Kehagias, Elias; Matthaiou, Nikolas; Samonakis, Dimitrios; Tsetis, Dimitrios
Hepatocellular carcinoma (HCC) is the sixth most common type of malignancy. Several therapies are available for HCC and are determined by stage of presentation, patient clinical status and liver function. Local–regional treatment options, including transcatheter arterial chemoembolization, radiofrequency ablation or microwave ablation, are safe and effective for HCC but are accompanied by limitations. The synergistic effects of combined transcatheter arterial chemoembolization and radiofrequency ablation/microwave ablation may overcome these limitations and improve the therapeutic outcome. The purpose of this article is to review the current literature on these combined therapies and examine their efficacy, safety and influence on the overall and recurrence-free survival in patients with HCC.